The Role of Decision Support Systems (DSS) in the Decision-Making Process : A Study of A Sample of Principals in the Colleges of the University of Mosul - سعيد مصطفى كامل; الكوسا عمر رهيف (PROSPECTIVE RESEARCHES, 2024)
The research aims to clarify the role of decision support systems in the decision-making process of the director - dean, associate dean, department head, division official, unit official - with a survey study in the year 2023 that relied on directors - administrative leaders - in the colleges of the Iraqi University of Mosul, where it was used statistical methods based on the statistical packages program (SPSS) to display and analyze the research results. The researchers collected data using the research sample’s answers to the questions of the questionnaire, which consisted of 40 questions that included paragraphs of variables distributed among 260 people included in the questionnaire. The response came to 245 questionnaires valid for analysis purposes. The research reached that decision support systems play a prominent role in providing a large amount of information necessary for managers to facilitate the process of making decisions quickly and accurately because they are linked to the daily and administrative life of institutions, as the current era is characterized by the rapid development of information and communications technology and keeping pace with the surrounding environment and competitors.